Spatial distribution of pesticides in surface water of the Estacas stream (Argentine Espinal region) associated with crop production - Van Opstal, Natalia Veronica (2023)
The Espinal region (Entre Ríos, Argentina) has sufered land use changes caused by expansion of the agricultural frontier. This expansion has led to an increased use of pesticides. This study is aimed at better understanding the spatial distribu tion of pesticides in surface water of the Estacas stream, a representative basin of the Espinal region, associated with crop production. The location and proportion of area with soybean, maize, and wheat crops in each catchment area of the basin were estimated, and surface water samples were taken to perform a pesticide screening during a period of one year. Soybean represented approximately 71% of the total cultivated area of the basin, whereas maize and wheat accounted for 15% and 14%, respectively. The analysis of 125 analytes showed the presence of 19 pesticides. The pesticide load maps showed that atrazine was detected in an area of relatively low catchment compared to other pesticides as glyphosate, which is applied in all the agricultural felds of the basin. The load of metolachlor and S-metolachlor covered a large area of the basin. The highest recorded concentrations of these pesticides were 86 μg L−1 of atrazine, 24 μg L−1 of metolachlor, 19 μg L−1 of glyphosate, and 15 μg L−1 of S-metolachlor. The results allow better understanding the environmental distribution of pesticides associ ated with pest control in the crops of the basin studied, the doses and times of application, and the variation in the rainfall in the basin. This study provides relevant information about how aquatic ecosystems in agricultural basins receive the difuse contribution of pesticides, representing potential sources of water pollution. Also, the results allow supporting the design of agricultural practices and politics to improve land-use planning for the development of sustainable basins.